2016
DOI: 10.1016/j.oraloncology.2015.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of dysphagia and quality of life (QOL) in comparable patients with HPV-positive oropharyngeal cancer receiving chemo-irradiation or cetuximab-irradiation

Abstract: Purpose Compare functional outcomes of radiotherapy (RT) concurrent with cetuximab (cet-RT) or with chemotherapy (chemo-RT) for comparable, good prognosis patients with Human Papillomavirus related (HPV+) oropharyngeal cancer (OPC). Methods Outcomes of patients with stage III/IV HPV+ OPC patients with minimal smoking history and non-T4/N3/N2C, treated on prospective protocol of RT concurrent with cetuximab (cet-RT), were compared to similar patients on prospective chemo-RT protocols. In both groups, videoflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…[31][32][33] However, there are limited prospective studies directly comparing outcomes for the 2 techniques to allow definitive conclusions at this time. 6,7,10,14,15,45,[48][49][50] Overall, results indicate there is a pattern of improved outcomes in the current study, with the exception of dysphagia and xerostomia. Similarly, Chen et al 47 found no statistical difference in acute mucositis, dysphagia, and xerostomia rates between helical tomotherapy IMRT and a step-and-shoot IMRT in a study of 149 patients with mixed tumor sites.…”
Section: Comparison With Linac Based Intensitymodulated Radiotherapmentioning
confidence: 48%
See 4 more Smart Citations
“…[31][32][33] However, there are limited prospective studies directly comparing outcomes for the 2 techniques to allow definitive conclusions at this time. 6,7,10,14,15,45,[48][49][50] Overall, results indicate there is a pattern of improved outcomes in the current study, with the exception of dysphagia and xerostomia. Similarly, Chen et al 47 found no statistical difference in acute mucositis, dysphagia, and xerostomia rates between helical tomotherapy IMRT and a step-and-shoot IMRT in a study of 149 patients with mixed tumor sites.…”
Section: Comparison With Linac Based Intensitymodulated Radiotherapmentioning
confidence: 48%
“…Although limited, direct comparison of the current results with key selected literature for patients with oropharyngeal SCC and oropharyngeal cancer undergoing traditional IMRT with concurrent chemotherapy, can also be seen in Table 4. 6,7,10,14,15,45,[48][49][50] Overall, results indicate there is a pattern of improved outcomes in the current study, with the exception of dysphagia and xerostomia. The rates of acute grade 3 mucositis found in the current study are similar or lower than those reported in the traditional IMRT literature.…”
Section: Comparison With Linac Based Intensitymodulated Radiotherapmentioning
confidence: 50%
See 3 more Smart Citations